Student motivation in learning through the use of the 21st- century learning activities - Mohd Isa, Nor Kalsum; Nordin, Noor Ayuni; Saari, Erni Marlina; Mohd Isa, Nor Junainah; Mohd Yunos, Mohd Yazid (UK Zhende Publishing Limited, 2023)
To materialize the country's aim of achieving the status of a developed country, the Malaysia government has carried out various agendas and observations from all angles and the field of the economy, including in the field of education. Thus, the stress on the concept of 4C1V(critical thinking, creativity, communication, collaboration, and good moral values) in Malaysia's education systems has been applied and because of that, the 21st-century learning comes into existence. This study aims to identify students' motivation level in learning through the use of 21st-century learning activities and evaluate the 21st-century learning activities that have a relationship with student motivation in learning. This study used a quantitative correlation approach by using a questionnaire form as the study instrument. A total of 90 students as respondents were involved in this study. The findings show that the student's motivation level through the use of 21st-century learning activities was at a high level. The think pair share activity is the one that is the most impactful to students' motivation. The finding is very significant to guide teachers in the implementation of 21st-centurylearning activities to enhance student motivation.